Local Culture-Based Multiliteracies Pedagogy with Digital Media to Improve Argumentative Writing Skills - Alia Alia; Iin Parlina; Nur Laili Mila Fitri (Yayasan Keluarga Guru Mandiri, 2025)
The ability to write coherent and persuasive argumentative essays is a critical academic skill for university students, yet many continue to face challenges in constructing logical claims, organizing evidence, and applying rhetorical strategies effectively. This study examines the effectiveness and classroom implementation of a local culture-based multiliteracies pedagogy model supported by digital media in improving students' argumentative writing skills in the Indonesian Language course. Employing a post-test only control group design, the research involved two classes: the experimental group received instruction integrating multiliteracies (visual, digital, textual, and cultural dimensions), local cultural content such as folklore and traditions, and digital media including videos and infographics, while the control group followed conventional instruction. Argumentative writing ability was measured through an essay test, and validity and reliability were ensured through expert review, item analysis, and inter-rater procedures. In addition to quantitative data, classroom observations and a teacher journal were analyzed qualitatively to capture how the pedagogy was implemented. Results indicate that students in the experimental group significantly outperformed those in the control group, and qualitative findings further reveal that cultural grounding, multimodality, and critical framing fostered deeper engagement, collaboration, and critical reasoning despite challenges of time management and digital literacy. The study concludes that this pedagogy provides a culturally responsive and digitally enriched model for strengthening academic literacy in higher education. This study advances the fields of multiliteracies and culturally responsive pedagogy by illustrating the empirical benefits of incorporating local culture and digital multimodal texts in improving students' argumentative writing skills in higher education.